Dancers’ Somatic of Musicality - Marinberg, Niv; Aviv, Vered (Frontiers in Psychology, 2019)
Dancers often perform while synchronizing their movements to music, as required by the choreographer. In this article, we introduce the concept of categorizing choreography (or segments of it), according to its relationship with either the rhythm or the melody of the accompanied music, or with both. We demonstrate this distinction through several examples for each category. In a pilot study, we composed choreographic sequences that were either melodic-based or rhythmic-based and taught them to professional dancers. The results showed that some dancers tend to synchronize their movements better to rhythm and others, to melody. We refer to this tendency as the “dancers’ somatic of musicality.” The findings highlight important differences in the somatic of musicality among dancers, requiring attention from both choreographs and dancers, since these differences have bearing on the way dancers learn, memorize, and perform.